The Influence of Economic Growth, Education, and Macroeconomic Factors on Regional Poverty Reduction - Dodo Kurniawan; Muh. Syahru Ramadhan (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The poverty rate in the region has consistently remained above 12% over the past five years, indicating a persistent socioeconomic challenge. This study aims to analyze the effect of population, economic growth, regional spending, inflation, and education on poverty levels by utilizing secondary data obtained from official national statistics and financial institutions. The method used is multiple regression analysis with the aid of SPSS 21 software. The findings show that population and inflation have a positive but statistically insignificant influence on poverty, while regional spending also exerts a positive and insignificant effect. In contrast, economic growth and education have a negative and statistically significant effect on poverty, with probability values of 0.003 and 0.042, respectively. Simultaneously, the five variables examined show a significant collective influence on poverty levels during the 2009–2023 period. These results emphasize that economic growth and education play key roles in poverty reduction. The study provides important insights for policymakers to formulate targeted, evidence-based strategies aimed at addressing poverty more effectively and sustainably in the long term.